Draft proceedings of East Africa Integrated River Basin Management Conference. [Vol.1] - Sokoine University of Agriculture (2005)
Themes: Water productivity - methodologies and management; Environmental flow assessment; Rainwater harvesting and micro irrigation; Water governance and institutions (conflicts, legal framework; tradeoffs, dialogue, community level management); Water economics and livelihoods; Modelling and Decision Aid Tools